ONLINE PEER MENTORING TO ENHANCE MATHEMATICAL PROBLEM-SOLVING STRATEGY AMONG INTROVERT AND EXTROVERT PERSONALITY - Wan Norliza Wan Bakar (Jurnal Penyelidikan Sains Sosial, 2021)
Mathematical problem solving is a process of constructing a mathematical modeland devising strategies to solve mathematical problems. There are many factors affectedstudent’s ability in problem solving. Personality is one of them. Due to this factor, a qualitativestudy is carried out on online peer mentoring in problem strategy among introvert and extrovertpersonality. 40 students participated. They have undergone (Myer Briggs Personality Test) andthe students are classified under 8 groups which consists of introvert and extrovert. Afteranswering the paper, the students were interviewed. The result of the study shows that onlinepeer mentoring for introvert and extrovert enhance the ability of the students in theirperformance.